Volcanic ash in dirt layers from the Allan Hills bare ice area in Victoria Land, Antarctica - Katsushima, Takayoshi; Nishio, Fumihiko (1985)
P(論文) Dirt layers were found in the Allan Hills bare ice area in Victoria Land, Antarctica. They contain volcanic ash consisting of abundant glass shards with subordinate crystal fragments of plagioclase, titanaugite, olivine, kaersutite, titanomagnetite, etc. Tephra samples collected from each of 8 dirt layers are classified into three groups based on the petrography, morphology and major element chemistry. Moreover, the major element chemistry of the glass shards indicates that these tephras comprise two rock series : one is evolved basanitoid series toward nephelinite, and the other basanitoid-trachybasalt-trachyte series. Accordingly, these tephras may have been derived from at least two different volcanoes. If the tephra sources are restricted to two volcanoes, the transportation distance of the tephras estimated from their grain size is less than 1000km. This estimation suggests that the tephra sources are restricted within Victoria Land. The tephras of basanitoid-trachybasalt-trachyte are similar in composition to some of the lavas of Quaternary volcanoes in Victoria Land. However, the tephras of the evolved basanitoid are different in composition from any Quaternary volcanic rocks hitherto reported from Antarctica. It will probably be confirmed in the future that some volcanoes in Victoria Land erupted such basanitoid ejecta. departmental bulletin paper